MicroRNA339 Targeting PDXK Improves Motor Dysfunction and Promotes Neurite Growth in the Remote Cortex Subjected to Spinal Cord Transection - Xiong, Liu-Lin; Qin, Yan-Xia; Xiao, Qiu-Xia; Jin, Yuan; Al-Hawwas, Mohammed; Ma, Zheng; Wang, You-Cui; Belegu, Visar; Zhou, Xin-Fu; Xue, Lu-Lu; Du, Ruo-Lan; Liu, Jia; et al. (Frontiers in Cell and Developmental Biology, 2020)
Spinal cord injury (SCI) is a fatal disease that can cause severe disability. Cortical reorganization subserved the recovery of spontaneous function after SCI, although the potential molecular mechanism in this remote control is largely unknown. Therefore, using proteomics analysis, RNA interference/overexpression and CRISPR/Cas9 in vivo and in vitro, we analyzed how the molecular network functions in neurological improvement, especially in the recovery of motor function after spinal cord transection (SCT) via the remote regulation of cerebral cortex. We discovered that the overexpression of pyridoxal kinase (PDXK) in the motor cortex enhanced neuronal growth and survival, and improved locomotor function in the hindlimb. In addition, PDXK was confirmed as a target of miR-339 but not miR-124. MiR-339 knock-out (KO) significantly increased the neurite outgrowth and decreased cell apoptosis in cortical neurons. Moreover, miR-339 KO rats exhibited functional recovery indicated by improved BBB score. Furthermore, bioinformatics prediction showed that PDXK was associated with GAP43, a crucial molecule related to neurite growth and functional improvement. The current research therefore confirmed that miR-339 targeting PDXK facilitated neurological recovery in the motor cortex of SCT rats, and the underlying mechanism was associated with regulating GAP43 in the remote cortex of rats subjecting to SCT. These findings may uncover a new understanding of remoting cortex control following SCI and provide a new therapeutic strategy for the recovery of SCI in future clinical trials.